Assessment of precision and reliability of a novel computerized heterophoria test - Wang, Yuwen; Zheng, Fuhao; Zhou, Fengchao; Song, E. (Frontiers in Neuroscience, 2023)
Purpose: To assess the precision and reliability of a novel computerized heterophoria test (CHT). Methods: One hundred and three subjects aged 20 to 48 (27.37 ± 5.15) were recruited from Wenzhou Medical University. All subjects with corrected spectacles were examined with CHT and a prism-neutralized objective cover test (POCT) in a randomized order, and then were re-examined with CHT within one week. Their heterophoria was measured at three different distances (3m, 0.77m and 0.4m); the average was recorded after three consecutive measurements. Inter-examiner repeatability, intra-examiner repeatability of CHT and agreement between CHT and POCT were evaluated. Results: There was no significant difference among repeated measurements using CHT (all p > 0.05). The difference between POCT and CHT was statistically significant at three distances (all p < 0.001). However, the mean absolute difference was 1.20△, 1.93△, and 2.41△, all of which were significantly smaller than the permissible range of error (4△) at three different distances (all p < 0.001). Conclusions: CHT had excellent inter- and intra-examiner repeatability, as well as a good correlation with POCT. The differences between CHT and POCT were within the permissible range of error. CHT could provide a precise and reliable measurement for clinical applications.